Integrating Local Wisdom into 21st Century Skills: A Contextual Framework for Culturally Relevant Pedagogy in Rural Classrooms - Ibnu Fitrianto; Muhammad Farisi (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study explores the integration of local wisdom into 21st-century education within rural classrooms, focusing on how culturally relevant pedagogy can enhance learning experiences and outcomes. By examining the intersection of local knowledge and the 4Cs (Critical Thinking, Communication, Collaboration, and Creativity), the research aims to identify effective instructional strategies and their impact on student engagement and academic success. Through qualitative methods, including interviews with teachers, observations, and community involvement, the study highlights the ways in which local wisdom—such as traditional stories, agricultural practices, and community values—is utilized in teaching practices. The findings suggest that the incorporation of these elements not only fosters deeper connections to the students' cultural identities but also cultivates essential skills for the 21st century. Additionally, the study discusses the challenges faced by educators in implementing these practices, including resource limitations and the need for professional development, while emphasizing the role of the local community in supporting the integration of culture into formal education. Ultimately, the research contributes to a more comprehensive understanding of how localized pedagogical approaches can be leveraged to create more inclusive, relevant, and engaging educational experiences in rural settings.